Pengaruh Video Animasi Terhadap Pengetahuan Dan Sikap Mahasiswa FKM UMI Tentang Jet Lag Sosial - Syabil Gema Syuhada; Yusriani; Andi Surahman Batara (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Social jet lag, which affects students' health and academic performance, is a significant concern linked to the mismatch between biological rhythms and social schedules. Heavy use of digital devices at night increases susceptibility to sleep disorders and social jet lag. This study aims to determine the effect of animated videos on students' knowledge and attitudes regarding social jet lag at the Faculty of Public Health, Muslim University of Indonesia. This study is quantitative, with a quasi-experimental pre-test and post-test design. The study was conducted among students of the Faculty of Public Health, Muslim University of Indonesia, class of 2025, with a sample of 15 respondents selected using simple random sampling. The intervention was given in the form of an educational animated video about social jet lag. Data were collected using a knowledge and attitude questionnaire that had been tested for validity and reliability, then analyzed using the Wilcoxon test. The results showed an increase in the proportion of knowledge in the sufficient category from 46.7% in the pre-test to 66.7% in the post-test. In addition, the proportion of positive attitudes increased from 33.3% to 60% after the intervention. The Wilcoxon test results showed a significant difference between pre-test and post-test scores for knowledge (p = 0.019) and attitude (p = 0.011). The intervention effect size was relatively large, at 0.61 for knowledge and 0.66 for attitude. This study concluded that the animated video was effective in improving students' knowledge and attitudes regarding social jet lag. The animated video can be used as a digital health promotion medium to raise students' awareness of the importance of managing healthy sleep patterns.